Efektivitas Antibakteri Ekstrak Pelepah Pisang Kepok Kuning terhadap Jumlah Koloni dan Warna Bakteri Serta Implementasi nya dalam Pembelajaran Biologi - Nafi, Afida Rafiud (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
The selection of yellow banana fronds as antibacterial material is due to the high content of flavonoids, saponins, and polyphenols. This study aims to determine the antibacterial power of Musa acuminata banana fronds based on the number of colonies and color of bacteria. Furthermore, banana fronds with various ethanol levels were tested for antibacterial power by maceration method which previously obtained simplisia, and tested in nutrient agar (NA) media. The results of this study are expected to obtain information about the potential of banana fronds as a natural antiseptic to reduce the number of bacterial colonies, as well as the color of bacteria observed in the study. Using a laboratory experimental research design with a complete randomized design (CRD) method, with 3 treatments, and 3 repetitions, the effective banana leaf extract used in this research is (0%, 5%, 10%, 15%). With the treatment design: P0 0% (as a control without giving banana leaf extract), P1 5% (0.5 gr of leaf extract + 10 ml of distilled water), P2 10% (1 gr of leaf extract + 10 ml of distilled water), P3 15% (1.5 gr of leaf extract + 10 ml of distilled water) Experiment Results Average Number of Bacterial Colonies 85.67 48 36.3 30.3 Average Observed Color Milk White Yellowish White, Yellowish White, Yellowish White. Based on this research, it can be concluded that: Yellow kepok banana leaf extract (Musa paradisiaca) as an antibacterial gives a real effect on the number of bacterial colonies as evidenced by the ANOVA test results, with a value of (42.520) ˃ 5% (4.067) and 1% (7.59). The best concentration of yellow kepok banana leaf extract for testing the number of bacterial colonies is at 15% yellow kepok banana leaf extract concentration (P3) with an average of 30.3 bacterial colonies. Yellow kepok banana leaf extract (Musa paradisiaca) affects the color of the observed bacteria, this is evidenced by the provision of variations in the color of the observed bacteria yellowish white, while the control remains milky white.